The challenges that the International Court of Justice has to face - Torrecuadrada García-Lozano, Soledad (2021)
In the article, we will identify some of the challenges that the ICJ has to face during the 75th anniversary of its inaugural session. Throughout the year, the Court has consolidated herself as an effective mechanism to resolve international disputed, however afterthree quarters of a century, the time has cometo identify which are the aspects that should be updated so that it continues to maintain itsutility throughout the 21stcentury.International society has evolved a lot since the Court began to function, so I consider that the time has come to study thestrengths and weaknesses that it has, in order to further thestrengthening the former and correcting the latter with the sole objective of adapting this dispute resolution mechanismchallenges to be addressed in the near future.